Apostasy Punishment In Islamic Scholarly Discourse: Perspectives And Implications In The Malaysian Context - Razali Musa; Kauthar Razali; Anis Sahira Mohamad Fakhrulrozi; Mohd Safri Ali; Muhammad Firdhaus Zulkifli; Nur Syahirah Mohammad Nasir (Universiti Sains Islam Malaysia, 2026)
Malaysian Journal of Syariah and Law, Volume 13 Issue 3 Page (637-651)